A Gestão do Conhecimento no contexto do teletrabalho em função da COVID-19 - Rômulo de Barros Teixeira (2022)
The pandemic caused by COVID-19 changed the routine of people and companies and made the use of information and communication technologies essential for the progress of a good part of professional, personal and educational activities. Due to the limitations of the encounter between people, an effective social interaction and exchange of experiences was greatly impaired. Given this scenario, a research was carried out based on a literature review in the SCOPUS database on knowledge management (KM) in the context of Telework, in order to demonstrate its advantages and ways to show it. For the development of the work, a mixed approach (simplified search of qualitative research) and descriptive level was carried out as a methodological procedure. The research priority was a technical approach, in order to provide accessories for qualitative research. In the first phase of the study, there was a survey of scientific articles recovered between the years 2019 and 2021 that deal with the KM function in the regulation of telework in social isolation. In the phase, there was a qualitative study through the analysis of the articles retrieved according to the selection, in order to those who spoke respectively of KM and Telework. The findings demonstrate that KM can be a possible solution for recording, using and disseminating the knowledge generated by employees.